Ultrasonic Characterisation of Porous Biomaterials Across Different Frequencies - Kohlhauser, C.; Hellmich, C.; Vitale-Brovarone, C.; Boccaccini, Aldo R.; Rota, A.; Eberhardsteiner, Josef (Strain, 2009)
Mechanical testing is the most common experimental technique to determine elastic stiffness of materials. In case of porous materials, especially such with very high porosity, the determination of material stiffness may be strongly biased by inelastic deformations occurring in the material samples, especially in the vicinity of the load transfer devices, such as loading platens. In contrast, ultrasonic waves propagating through a material generate very small stresses and strains (and also strain rates lying in the 'quasistatic' regime). Thus, they enable the direct determination of the components of elastic stiffness tensors of materials, and also of those with a very high porosity. We shortly revisit from the theoretical basis of continuum (micro)mechanics that, depending on the frequency of the employed acoustical signals, the investigated materials are characterised at different observation scales, e.g. the elasticity of the overall porous medium, or that of the solid matrix inside the material are determined. We here report the elastic properties of biomaterials and biological materials at different length scales, by using ultrasound frequencies ranging from 100 kHz to 20 MHz. We tested isotropic scaffolds for biomedical engineering, made up of porous titanium and two different bioactive glass-ceramics, and we also determined the direction-dependent normal and shear stiffness components of the anisotropic natural composite 'spruce wood'. © 2009 The Authors.
UnivIS-Import:2015-03-09:Pub.2009.tech.IW.LM.ultras
Keywords: Porous biomaterials; Stiffness tensor components; Ultrasound; Wood